Adding ammonia during Fischer-Tropsch Synthesis: Pathways to the formation of N-containing compounds - De Vries, Christian (Centre for Catalysis Research, 2017)
The Fischer-Tropsch synthesis (FTS) process, better known for its ability to produce synthetic fuel via the hydrogenation of CO, has shown potential to produce valuable chemicals when ammonia is added to the feed. In this work certain aspects of the pathway to the formation of N-containing compounds that form when NH₃ is added during FTS, using mostly iron based catalysts is investigated. In addition, the effect this has on the FTS reaction itself is evaluated. To achieve this goal, both theoretical and experimental techniques are used in this study. The CO adsorption and dissociation reactions are assumed to be important elementary reactions for many proposed FTS pathways. In the theoretical part of this thesis, spin-polarized periodic density functional theory (DFT) calculations are employed to study aspects of the initial stage of the pathway on a model Fe(100) surface. Considering the formation of N-containing hydro- carbons, one would assume that NH₃ initially adsorbs and dissociates on the catalyst surface, which could take place in the presence of CO. The surface chemistry of these adsorbates is well studied both experimentally and theoretically, but their co-existence has not yet been evaluated on model Fe surfaces. Initially a platform is generated by calculating the individual potential energy surfaces (PES) for the decomposition of CO and NH₃ on Fe(100) at a coverage of ϴ = 0.25 ML. These calculations provided the basis for comparing the adsorption and dissoci- ation profiles of CO and NH₃ on the Fe(100) surface via the use of the same computational methodology, and importantly making use of the same exchange correlation functional (RPBE) for both adsorbates. Furthermore, it was desired to evaluate the kinetics and thermodynamics of the NH₃ decomposition on the Fe(100) surface at relevant temperatures and pressures (by combining the DFT results with statistical thermodynamics) to better understand the role of NHₓ surface species involved in the pathway to the formation of the N-containing compounds on a model catalyst surface. The DFT results that are reported for the individual decomposi- tion PES for CO and NH₃ were generally found to be in close agreement with what has been reported in previous DFT studies and deduced experimentally for the relevant adsorption and decomposition pathways. The resulting Gibbs free energies for the PES suggests that NH₂ may be kinetically trapped on the Fe(100) surface at a coverage of ϴ = 0.25 ML and the reaction conditions (T = 523 K and p*NH₃ = 0.2 bar) where NH₃ is co-fed with synthesis gas during FTS. The individual adsorptions of CO and NHₓ (with x = 3, 2, 1, 0) were compared to their coadsorbed states, by calculating the heat of mixing (ΔEmix) and the activation barriers (Eₐ) for CO dissociation in the presence and absence of the NHₓ surface species on the Fe(100) sur- face. Similar to the individual adsorption of NH₃, the 0 K regime inherent to DFT calculations is bridged by calculating the Gibbs free energy of mixing for CO + NH₃ on Fe(100) at higher temperatures. Both repulsive and attractive interaction energies were calculated for the various coadsorbed states (CO + NHₓ on Fe(100)) and similarly some configurations resulted in an energetically favored or unfavored heat of mixing. The activation barrier for CO dissociation was lowered when coadsorbed with NH₃ and NH₂, and raised when coadsorbed with NH and N. With all the coadsorbed structures the CO dissociation reaction became more endothermic. Previous experimental studies have shown a concomitant reduction in oxygenate selectivity with an increase in the selectivity for N-containing compounds, when NH₃ is added during FTS. It is well-known that oxygenates undergo secondary reactions when using iron-based catalysts in FTS. In addition, the catalyst used in aforementioned studies (precipitated Fe/K) are active for the amination reactions of oxygenates. It is therefore hypothesized that some oxygenates pro- duced via the primary FTS pathway are converted to N-containing compounds via a secondary reaction. The experimental part of this thesis is therefore aimed at testing this hypothesis. A base case study included a comparison between a Fe-catalyzed slurry phase FTS reaction and a FTS reaction with all parameters remaining unchanged, except for the addition of 1 vol % NH₃ to the syngas (CO + H₂) feed. The activity (CO and H₂ conversion) data collected did not reveal any appreciable loss in the rate of the FTS reaction when 1 vol % NH₃ was added and steady state was reached (, that is after 48 hours time on stream (TOS)). A slower carburization period was however observed when comparing the CO conversion during the first 24 hours TOS, and further supported by the slow increase in CO₂ selectivity during the same period. The use of two-dimensional gas chromatography (GC × GC-TOF/FID) allowed for the discovery of a formation of a range of secondary and tertiary amines, not reported in previous studies. The expected loss in oxygenate selectivity was observed and further probed by co-feeding 1-octanol with the feed (CO + 2H₂ + 1 vol % NH₃) via a saturator. These results clearly indicated a significant loss in oxygenate formation as a result of secondary conversion to N-containing compounds. Questions regarding the stability of aliphatic nitriles prompted the co-feeding of nonanitrile under similar conditions. The results obtained after co-feeding nonanitrile, sug- gests that nonanitrile is readily converted to secondary and tertiary amines and that the ratios of aliphatic alcohols and nitriles are close to equilibrium. The use of CO₂ as carbon source, the investigation of the product spectrum at higher space velocities and the use of Rh-based catalysts, when NH₃ is added during FTS were included in shorter studies. The combination of these results, adds to the knowledge pool for the case where NH₃ is present in the FTS regime, as a poison or reactant. Additional information regarding the path to the formation of N-containing compounds was obtained via the detailed analysis of the product spectra with two-dimensional gas chromatography and the subsequent co-feeding reactions. The results ob- tained via co-feeding reactions, can be used to devise strategies to increase the selectivity of the desired N-containing compounds.